Perbandingan Sekuens Konsensus Gen Hemaglutinin Virus Avian Influenza Subtipe H5N1 Asal Unggas di Indonesia dengan Subtipe H5N2 dan H5N9 - Kade Mahardika, I Gusti Ngurah; Suartha, I Nyoman; Suardana, Ida Bagus Kade; Yuniati Kencana, I Gusti Ayu; Teguh Wibawan, I Wayan (Jurnal Veteriner; Vol 10 No 1 (2009))
Consensus sequence of hemagglutinin (HA) gene of avian influenza viruses of H5N1 subtype isolatedfrom fowl in Indonesia – hereafter named as H5N1_Indonesia – is compared with that of H5N2 and H5N9viruses. Sequence information were downloaded from the public database GeneBank. The genetic distancesand nucleotide as well as its deduced amino-acid sequence alignment were analysed. At nucleotide level,genetic distances of HA between H5N1_Indonesia to H5N2 and H5N9 are 16.2% and 9.6%, respectively.At amino-acid level, the distances are 9.7% and 6.8%. The genetic distances of HA1 fragments are 19.0%(H5N1_Indonesia – H5N2) and 10.9% (H5N1_Indonesia – H5N9). At amino-acid, level the genetic distancesof HA1 are 13.1% (H5N1_Indonesia-H5N2) and 8.8% (H5N1_Indonesia – H5N9). All three subtypes havedifferent glycosilation motive and variation of amino-acid sequence of four antigenic sites. The consequenceof those facts is discussed.